The Role of Principal Leadership, Incentives, and Emotional Intelligence in Improving Teacher Performance at SMA Negeri 1 Karang Baru, Aceh Tamiang - Aisyah, Nur; Julianda, Rizky; Kurniawan, Dodi; Sabungan Lubis, Mulia Hoge; Supratman, Ali; Lubis, Hasrita (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2024)
This study aims to analyze the influence of principal leadership, incentives, and emotional intelligence on teacher performance at SMA Negeri 1 Karang Baru, Aceh Tamiang. This study uses a quantitative method with a descriptive-correlational approach. The sample of this study is 44 teachers, who were selected using a simple random sampling technique. Data was collected through questionnaires that had been tested for validity and reliability, then analyzed using multiple regression. The results of the study show that principal leadership, incentives, and emotional intelligence have a positive and significant effect on teacher performance, both partially and simultaneously. The principal's leadership had the most dominant influence with a regression coefficient of 0.351, followed by emotional intelligence with a coefficient of 0.310, and incentives with a coefficient of 0.282. Simultaneously, these three variables explain 62.7% of the variation in teacher performance. In conclusion, good principal leadership, the provision of appropriate incentives, and high emotional intelligence play an important role in improving teacher performance. The recommendations given are increased leadership training, evaluation of incentive systems, and development of teachers' emotional intelligence to improve the quality of teaching in schools.